2023
DOI: 10.3390/jmse11061205
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Highly Compatible Underwater Wireless Power Transfer Station for Seafloor Observation Equipment

Abstract: Conventional cabled seafloor observatories (CSOs) power in-situ instruments via wet-mated or dry-mated direct electrical contact (DEC) connectors to achieve long-term and real-time observation. However, the DEC connectors have high risks of water leakage and short circuits in power feeding, especially under high water pressure. This paper proposes a highly compatible underwater station based on inductive wireless power transfer (IPT) technology to address the above reliability issue. A novel energy transmitter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…(5) The range of load voltages is between 5 V and 10 V, which can be used to charge batteries for small underwater submarines [43]. (6) The coil size used in [34] is similar to that used in this paper, but it is more focused on short-range transfer, and it resonates at 373 kHz, while the work in [44] was also carried out at midrange (like this paper), but with a smaller-sized coil that resonates at 570 kHz. It is concluded that the frequency that distinguishes between different transfer conditions in seawater and air is related to the size of the coil and the transfer distance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) The range of load voltages is between 5 V and 10 V, which can be used to charge batteries for small underwater submarines [43]. (6) The coil size used in [34] is similar to that used in this paper, but it is more focused on short-range transfer, and it resonates at 373 kHz, while the work in [44] was also carried out at midrange (like this paper), but with a smaller-sized coil that resonates at 570 kHz. It is concluded that the frequency that distinguishes between different transfer conditions in seawater and air is related to the size of the coil and the transfer distance.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the conventional charging method, wireless power transfer (WPT) technology is garnering increasing attention as a result of the discarding of the traditional wire bondage, making the charging power supply and charging equipment completely isolated, and better solving the problems of exposed wires, easily produced contact sparks, and poor mobility that exist in wired electrical power transfer [1][2][3][4][5][6][7]. It has been widely employed in electric vehicles [8,9], medical equipment, portable electronic devices, aerospace applications, and ocean-related applications.…”
Section: Introductionmentioning
confidence: 99%
“…These configuration are used to charge only one device and have the advantage of allowing a higher misalignment. Some of the recent studies on these configurations can be found in [226][227][228]. In [226], they achieved a power transfer of 884 W with a 94.3% efficiency, and in [227], a power transfer of 1.5 kW with an efficiency of 89.8%.…”
Section: Innovative Topologies and Multi-coil Systemsmentioning
confidence: 99%
“…Explorations in these areas have unveiled new species and remarkable biotechnological applications. Through the implementation of numerical simulations and laboratory experiments, researchers have unraveled the mechanics and dynamics of fluid flow and heat transfer within these ecosystems [9,10] . These insights illuminate the processes that sustain these extraordinary habitats, offering valuable lessons for sustainable management and utilization of marine resources.…”
Section: Dear Readers Of and Contributors To Marine And Environmentmentioning
confidence: 99%